2012
DOI: 10.2478/v10188-012-0013-3
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial activity of selected lactic acid cocci and production of organic acids

Abstract: Antimicrobial activity of selected lactic acid cocci and production of organic acidsAntimicrobial activity and production of organic acids by selected lactic acid bacteria were monitored in this study. The largest antimicrobial activity against indicator microorganisms showed Pediococcus sp. G5, whereasStreptococcus thermophilushad no inhibitory effect. The inhibitory effect ofPediococcussp. G5 was strongest against Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 18 publications
3
9
0
2
Order By: Relevance
“…Maleic and ascorbic acids were detected in lower quantities compared with the other organic acids. Hladíková et al (2012) reported similar results; they produced lactic acid, acetic and succinic acids from some lactic acid strains. Lactic acid concentration was 2.877-15.2829 g/L while acetic and succinic acids concentration were 0.696-0.954 g/L and 0.187-0.421 g/L, respectively.…”
Section: Hplc Analysis Of Organic Acidssupporting
confidence: 52%
See 1 more Smart Citation
“…Maleic and ascorbic acids were detected in lower quantities compared with the other organic acids. Hladíková et al (2012) reported similar results; they produced lactic acid, acetic and succinic acids from some lactic acid strains. Lactic acid concentration was 2.877-15.2829 g/L while acetic and succinic acids concentration were 0.696-0.954 g/L and 0.187-0.421 g/L, respectively.…”
Section: Hplc Analysis Of Organic Acidssupporting
confidence: 52%
“…The obtained results showed clearly that lactic acid bacteria produce substances, which have ability to inhibit or prevent the growth of foodcontaminating fungi. Many reports have suggested that antifungal activity is a combination of organic acids such as lactic, acetic, and phenyllactic acid (Yang and Clausen 2005;Hladíková et al, 2012) or bacteriocins (Mortvedt et al, 1991) and low molecular weight antimicrobial agents and peptides (Strom et al, 2002). El Sanhoty (2008) suggested that the antifungal effect of LAB could not simply the result of low pH, but is most probably due to the formation and secretion of pH dependent antifungal metabolites.…”
Section: Efficacy Of Lab For Inhibition Pathogenic Bacteriamentioning
confidence: 99%
“…Antimicrobial effect of diacetyl, acetic acid and propionic acid against Salmonella typhimurium , Escherichia coli , S. aureus and Listeria monocytogenes has also been evaluated [ 32 , 33 ]. Regarding phenyllactic acid, produced by several LAB genera [ 34 ], it displayed both bactericidal (against L. monocytogenes and S. aureus ) [ 35 ] and antifungal effects [ 36 ]. As described, the organic acids produced by LAB contribute to the safety of foods by creating an adverse environment (by low pH) that interferes in the cell membrane permeability.…”
Section: Use Of Starter Cultures To Improve the Food Safety In Fermentioning
confidence: 99%
“…Uma alternativa para padronizar e melhorar os atributos de qualidade do queijo de manteiga, e ao mesmo tempo aproximar o seu processo de fabricação àquele que o originou, consiste no uso de culturas lácteas iniciadoras para acidificar o leite, e produzir o coágulo a ser fundido. O uso de bactérias lácticas iniciadoras pode ser vantajoso na elaboração do queijo de manteiga porque além delas converterem a lactose a ácido láctico necessário para reduzir o pH do leite (Goktepe, 2006;Walstra, et al, 2006), elas também produzem compostos aromáticos desejáveis, tais como diacetil, acetoína, e acetaldeído (Hladíková, et al, 2012), e uma ampla variedade de metabólitos antimicrobianos (Gálvez, et al, 2007).…”
Section: Introductionunclassified